The Effect of Leadership Style and Work Environment on Employee Performance of Bnctl Branch Banks (Banco Nacional De Comercio De Timor-Leste) - Victoria Araujo de Almeida; Hermien Tridayanti; Mochammad Arif (IJEBD (International Journal of Entrepreneurship and Business Development), 2019)
Purpose: This study aims to analyze the Effect of Leadership Style and Work Environment on Employee Performance of the Bank Branch Branch (Banco Nacional De Comercio De Timor-Leste) partially and simultaneously. Design/methodology/approach: This study is quantitative. Findings: Keywords: Leadership Style, Work Environment, Employee Performance. Research limitations/implications: 30 employees from all employees in he Bank Branch Branch (Banco Nacional De Comercio De Timor-Leste) Practical implications: The results of this study indicate that leadership style (X1) does not have a significant effect of 0.224 partially on Employee Performance (Y) and Work Environment (X2) with a significant effect of 0.004 on Employee Performance (Y). Originality/value: Paper type: This paper can be categorized as case study paper.